2021
DOI: 10.1080/23311975.2021.1891661
|View full text |Cite
|
Sign up to set email alerts
|

Understanding behavioral intention to use mobile wallets in vietnam: Extending the tam model with trust and enjoyment

Abstract: Mobile wallet (M-wallet), as an innovative alternative payment, is trendy in developed economies because it provides users with the ease, safety, and fast completion of daily financial activities. However, M-wallets have still been seen in the infancy stage in Vietnam. Therefore, the study aims to discover the main factors shaping behavioral intention to use mobile wallets in Vietnam. The extended version of the Technology Acceptance Model (TAM) with perceived enjoyment and trust was considered as a theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
103
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 59 publications
19
103
0
6
Order By: Relevance
“…Additionally, it has been demonstrated that PU has a beneficial effect on the attitude toward using e-wallets, followed by the intention of using them (Shankar & Datta, 2018;To & Trinh, 2021;Yang et al, 2021). This usefulness may be enhanced by augmenting additional services to make users enjoy using e-wallets as an alternative payment method, particularly in order to contain the spread of COVID-19.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Additionally, it has been demonstrated that PU has a beneficial effect on the attitude toward using e-wallets, followed by the intention of using them (Shankar & Datta, 2018;To & Trinh, 2021;Yang et al, 2021). This usefulness may be enhanced by augmenting additional services to make users enjoy using e-wallets as an alternative payment method, particularly in order to contain the spread of COVID-19.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…The demand for eWallets is linked to the public's desire to engage in mobile payments and enjoy the benefit of cashless transactions using a digital form of a physical wallet (Phuong et al. , 2020; To and Trinh, 2021). As a result of this demand, mainly in developing countries, the overall usage rate of eWallets grew by 7% globally in 2020, and it is estimated that about half of all sales related to e-commerce will be based on eWallets by 2023 (Snider, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to a high degree of uncertainty, trust becomes a significant factor for users to use mobile technology ( Nguyen & Nguyen, 2020 ). Past studies found that trust significantly impacts consumer behaviour (intention and adoption) in uncertain environments ( To & Trinh, 2021 ). Furthermore, Gbongli et al (2020) confirmed that customer’s trust positively impacts customer’s intention to use electronic banking.…”
Section: Resultsmentioning
confidence: 99%
“… Venkatesh et al (2012) defined perceived enjoyment as “the fun, pleasure, entertainment, or playfulness derived from using a technology”, and it found that it has a significant effect on consumer's technology acceptance. To and Trinh (2021) introduced perceived enjoyment as “the degree to which a person feels enjoyable when using e-wallets”. Previous studies empirically incorporated perceived enjoyment to the TAM and confirmed that this construct positively impacts behavioural intention (To).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation